Study protocol for FAXAge: a randomized, controlled clinical trial of fasting and exercise to slow aging in humans - Emma Bundgård Fals; Emilie Caroline Springborg; Adam Bjørnholdt Berthelsen; Jonas Nyeman-Nielsen; Steen Larsen; Morten Scheibye-Knudsen (GeroScience, 2026)
Biomarkers of aging, particularly DNA methylation-based clocks, have shown promise as tools to assess whether interventions may impact the rate of biological aging. Among possible interventions physical exercise has shown protective effects against many age-associated diseases, while time-restricted feeding (TRF) has shown metabolic benefits in preclinical models. The combined effect of exercise and TRF on aging biomarkers remains largely unexplored. In this 52-week four-armed, randomized, controlled trial (clinicaltrials.gov: NCT07207044) 240 healthy adults aged 65 and above will be allocated to four groups: combined cardio and strength training (EXE), TRF, combined EXE and TRF, or control. Participants will undergo assessments at baseline, 3, 6, and 12 months, with follow-ups at 2, 5, and 10 years. The primary outcome measure is Dunedin Pace of Aging DNA methylation age with secondary measures including RNA-sequencing, metabolomics, inflammatory markers, microbiome analysis, cognitive and physical measures. By deeply phenotyping participants, the Fasting And eXercise (FAXAge) study will provide novel insights into whether TRF, EXE, or a combination can slow or reverse biological aging in older adults.